An Assessment of the National Institute of Standards and Technology Measurement and Standards Laboratories, Fiscal Year 1998 (The National Academies Press, 1998)

Research Reactor Aluminum Spent Fuel: Treatment Options for Disposal - National Research Council (The National Academies Press, 1998)
The U.S. Department of Energy (DOE) is preparing an environmental impact statement (EIS) for management of aluminum spent fuel from foreign and domestic research reactors, much of which is highly enriched in uranium-235. This EIS will assess the need for additional treatment and storage facilities at the Savannah River Site to accommodate the receipt of this fuel, and it also will assess and select a treatment technology to prepare this fuel for interim storage and eventual shipment to a repository for disposal. This National Research Council book, which was prepared at the request of DOE's Savannah River Office, provides a technical assessment of the technologies, costs, and schedules developed by DOE for eight alternative treatment options and the baseline reprocessing option. It also provides comments on DOE's aluminum spent fuel disposal program, a program that is slated to last for about 40 years and cost in excess of $2 billion.
Keywords: Environment and Environmental Studies

International Benchmarking of US Materials Science and Engineering Research (The National Academies Press, 1998)
Keywords: Engineering and Technology

Ceramic Fibers and Coatings: Advanced Materials for the Twenty-First Century - National Research Council (The National Academies Press, 1998)
High-temperature ceramic fibers are the key components of ceramic matrix composites (CMCs). Ceramic fiber properties (strength, temperature and creep resistance, for example)-along with the debonding characteristics of their coatings-determine the properties of CMCs. This report outlines the state of the art in high-temperature ceramic fibers and coatings, assesses fibers and coatings in terms of future needs, and recommends promising avenues of research. CMCs are also discussed in this report to provide a context for discussing high-temperature ceramic fibers and coatings.
Keywords: Engineering and Technology

Separation Technologies for the Industries of the Future - National Research Council (The National Academies Press, 1998)
Separation processes—or processes that use physical, chemical, or electrical forces to isolate or concentrate selected constituents of a mixture—are essential to the chemical, petroleum refining, and materials processing industries. In this volume, an expert panel reviews the separation process needs of seven industries and identifies technologies that hold promise for meeting these needs, as well as key technologies that could enable separations. In addition, the book recommends criteria for the selection of separations research projects for the Department of Energy's Office of Industrial Technology.
Keywords: Math, Chemistry, and Physics

Technology Commercialization: Russian Challenges, American Lessons (The National Academies Press, 1998)
This collection of papers—by American and Russian specialists—addresses a variety of legal, regulatory, institutional, and financial issues that can promote or hinder technology commercialization. The book is the result of a series of workshops organized by the National Research Council with the Russian Academy of Sciences on commercialization of technologies, particularly those developed at research and educational institutions. Technology Commercialization concludes with a list of actions, programs, and policies which warrant further consideration as Russia tries to improve the success of technology commercialization. This book will be of interest to those concerned with small-business development in post-communist states, university technology management, and comparative technology commercialization.
Keywords: Industry and Labor; Biology and Life Sciences

Review of the Research and Development Plan for the Office of Advanced Automotive Technologies - National Research Council (The National Academies Press, 1998)
Keywords: Transportation and Infrastructure; Energy and Energy Conservation

Seismic Signals from Mining Operations and the Comprehensive Test Ban Treaty: Comments on a Draft Report by a Department of Energy Working Group - National Research Council (The National Academies Press, 1998)
Keywords: Earth Sciences; Conflict and Security Issues; Energy and Energy Conservation

Assessing the Need for Independent Project Reviews in the Department of Energy (The National Academies Press, 1998)
Keywords: Engineering and Technology

The Ecology of Industry: Sectors and Linkages - National Academy of Engineering (The National Academies Press, 1998)
This volume provides insights into the environmental practices of five industry sectors: materials processing, manufacturing, electric utilities, and pulp and paper. The ecology of industry is presented in terms of systems of production and consumption, taking into account the flows of material, energy, capital, and information. The book examines ways to improve the environmental performance of these industries (and others, such as the service sector) and shows how decisions made by industry managers can leverage systemic environmental improvements elsewhere in the economy.
Keywords: Environment and Environmental Studies; Industry and Labor

Frontiers of Engineering: Reports on Leading Edge Engineering from the 1997 NAE Symposium on Frontiers of Engineering - National Academy of Engineering; National Academy of Engineering (The National Academies Press, 1998)
Space may have been called the final frontier, but there are new frontiers to discover every day, and engineers are the ones exploring them. Through groundbreaking research and new technologies, engineers are able to go beyond traditional boundaries to do things that would have been all but impossible just a few years ago. This book, the most recent in a series of publications, describes new and emerging technologies and explains how they were developed and the benefits they will bring. It also offers highlights of the pioneering research and technological work being done by some of the country's emerging leaders in engineering. Topics include biomechanics, sensors and control for manufacturing processes, safety and security issues, decisionmaking tools for design and manufacturing, and intelligent transportation systems.
Keywords: Engineering and Technology

National Automated Highway System Research Program: A Review: A Review -- Special Report 253 - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 1998)
TRB Special Report 253 - National Automated Highway System Research Program: A Review assesses the appropriateness of the original vision and mission of the National Automated Highway System Research Program, the National Automated Highway System Consortium's (NAHSC's) results and the effectiveness of the approach taken by NAHSC in carrying out its charge, and the role of the consortium in future research on intelligent vehicles.Perhaps the most ambitious ITS concept advanced in ISTEA was the proposed development of automated highways. Automated highways were envisioned as increasing throughput dramatically while simultaneously reducing crashes. In ISTEA, Congress challenged USDOT to create, test, and select a prototype automated highway system within 7 years. To this end, a public–private consortium was formed to develop and test automation concepts. Those concepts were demonstrated in San Diego, California, in 1997.Although the demonstration showcased some exciting technologies, the committee that reviewed the national automated highway research program found that daunting technical, social, and institutional issues would have to be addressed before such a system could become a reality in any metropolitan area. For example, although the demonstrated technologies would enable remarkably high throughput on high-volume urban Interstates feeding into the heart of a congested urban area, they could not resolve the complex problem of allocating these increased traffic volumes safely and efficiently into the traffic streams of already congested local streets. Even so, the committee urged USDOT to continue to explore the potential for using automation in specific circumstances, as well as the possibilities for developing vehicle-based safety-enhancing technologies for cars, trucks, and transit vehicles.
Keywords: Transportation and Infrastructure

Biographical Memoirs: Volume 74 - National Academy of Sciences (The National Academies Press, 1998)
Biographic Memoirs: Volume 74 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.
Keywords: Biography and Autobiography; Biology and Life Sciences

Assessing the Value of Research in the Chemical Sciences - National Research Council (The National Academies Press, 1998)
This book captures the messages from a workshop that brought together research managers from government, industry, and academia to review and discuss the mechanisms that have been proposed or used to assess the value of chemical research. The workshop focused on the assessment procedures that have been or will be established within the various organizations that carry out or fund research activities, with particular attention to the Government Performance and Results Act (GPRA). The book presents approaches and ideas from leaders in each area that were intended to identify new and useful ways of assessing the value and potential impact of research activities.
Keywords: Math, Chemistry, and Physics

Containing the Threat from Illegal Bombings: An Integrated National Strategy for Marking, Tagging, Rendering Inert, and Licensing Explosives and Their Precursors - National Research Council (The National Academies Press, 1998)
In response to the rising concern of the American public over illegal bombings, the Bureau of Alcohol, Tobacco, and Firearms asked the National Research Council to examine possible mechanisms for reducing this threat. The committee examined four approaches to reducing the bombing threat: addition of detection markers to explosives for pre-blast detection, addition of identification taggants to explosives for post-blast identification of bombers, possible means to render common explosive materials inert, and placing controls on explosives and their precursors. The book makes several recommendations to reduce the number of criminal bombings in this country.
Keywords: Conflict and Security Issues

Maintaining U.S. Leadership in Aeronautics: Breakthrough Technologies to Meet Future Air and Space Transportation Needs and Goals - National Research Council (The National Academies Press, 1998)
After the completion of the National Research Council (NRC) report, Maintaining U.S. Leadership in Aeronautics: Scenario-Based Strategic Planning for NASA's Aeronautics Enterprise (1997), the National Aeronautics and Space Administration (NASA) Office of Aeronautics and Space Transportation Technology requested that the NRC remain involved in its strategic planning process by conducting a study to identify a short list of revolutionary or breakthrough technologies that could be critical to the 20 to 25 year future of aeronautics and space transportation. These technologies were to address the areas of need and opportunity identified in the above mentioned NRC report, which have been characterized by NASA's 10 goals (see Box ES-1) in "Aeronautics & Space Transportation Technology: Three Pillars for Success" (NASA, 1997). The present study would also examine the 10 goals to determine if they are likely to be achievable, either through evolutionary steps in technology or through the identification and application of breakthrough ideas, concepts, and technologies.
Keywords: Space and Aeronautics

People and Pixels: Linking Remote Sensing and Social Science - National Research Council (The National Academies Press, 1998)
Space-based sensors are giving us an ever-closer and more comprehensive look at the earth's surface; they also have the potential to tell us about human activity. This volume examines the possibilities for using remote sensing technology to improve understanding of social processes and human-environment interactions. Examples include deforestation and regrowth in Brazil, population-environment interactions in Thailand, ancient and modern rural development in Guatemala, and urbanization in the United States, as well as early warnings of famine and disease outbreaks. The book also provides information on current sources of remotely sensed data and metadata and discusses what is involved in establishing effective collaborative efforts between scientists working with remote sensing technology and those working on social and environmental issues.
Keywords: Earth Sciences

Biographical Memoirs: Volume 75 - National Academy of Sciences (The National Academies Press, 1998)
Biographical Memoirs is a series of essays containing the life histories and selected bibliographies of deceased members of the National Academy of Sciences. The series provides a record of the life and work of some of the most distinguished leaders in the sciences, as witnessed and interpreted by their colleagues and peers. They form a biographical history of science in America—an important part of our nation's contribution to the intellectual heritage of the world.
Keywords: Biography and Autobiography